Impaired Redox Signaling in Huntington’s Disease: Therapeutic Implications - Paul, Bindu D.; Snyder, Solomon H. (Frontiers in Molecular Neuroscience, 2019)
Huntington’s disease (HD) is a neurodegenerative disease triggered by expansion of polyglutamine repeats in the protein huntingtin. Mutant huntingtin (mHtt) aggregates and elicits toxicity by multiple mechanisms which range from dysregulated transcription to disturbances in several metabolic pathways in both the brain and peripheral tissues. Hallmarks of HD include elevated oxidative stress and imbalanced redox signaling. Disruption of antioxidant defense mechanisms, involving antioxidant molecules and enzymes involved in scavenging or reversing oxidative damage, have been linked to the pathophysiology of HD. In addition, mitochondrial function is compromised in HD leading to impaired bioenergetics and elevated production of free radicals in cells. However, the exact mechanisms linking redox imbalance to neurodegeneration are still elusive. This review will focus on the current understanding of aberrant redox homeostasis in HD and potential therapeutic interventions.